Stillbirth in Australia 1: The road to now: Two decades of stillbirth research and advocacy in Australia. Issue 6 (November 2020) - Flenady, Vicki J.; Middleton, Philippa; Wallace, Euan M.; Morris, Jonathan; Gordon, Adrienne; Boyle, Frances M.; Homer, Caroline SE; Henry, Sarah; Brezler, Leigh; Wojcieszek, Aleena M.; Davies-Tuck, Miranda; Coory, Michael; et al.
Abstract: Stillbirth is a major public health problem with an enormous mortality burden and psychosocial impact on parents, families and the wider community both globally and in Australia. In 2015, Australia's late gestation stillbirth rate was over 30% higher than that of the best-performing countries globally, highlighting the urgent need for action. We present an overview of the foundations which led to the establishment of Australia's NHMRC Centre of Research Excellence in Stillbirth (Stillbirth CRE) in 2017 and highlight key activities in the following areas: Opportunities to expand and improve collaborations between research teams; Supporting the conduct and development of innovative, high quality, collaborative research that incorporates a strong parent voice; Promoting effective translation of research into health policy and/or practice; and the Regional and global work of the Stillbirth CRE. We highlight the first-ever Senate Inquiry into Stillbirth in Australia in 2018. These events ultimately led to the development of a National Stillbirth Action and Implementation Plan for Australia with the aims of reducing stillbirth rates by 20% over the next five years, reducing the disparity in stillbirth rates between advantaged and disadvantaged communities, and improving care for all families who experience this loss.